Coping Techniques of Local People to Flood and River Erosion in Char Areas of Bangladesh (Journal of Environmental Science and Natural Resources, 2013)
This study is designed to explore the local people survival strategies and assesses variation in peoples ability to cope with flood and riverbank erosion of two char land (Mid-channel Island) villages of Bangladesh. The data were collected by the application of social survey, key informant interview, focus group discussions and field observation. Most of the people of the char land villages were affected by both flood and river erosion. The result of the study showed that devastating river erosion occurred in Shushua char as compared with Degreer char in 2010 and people tried to adapt with adverse situation by their own techniques. People of both the chars were experienced flooding more than two months in the same year. Households ability to adapt with flood and river erosion depends on peoples socioeconomic and environmental conditions, such as education, income and occupation. Though, flood and river erosion cause the loss of lives and properties, peoples indigenous coping techniques could significantly reduced their vulnerability without outside assistance. Effective early warning system, integrate local coping practice with modern technology and improve socioeconomic condition in a sustainable way are necessary to reduce the losses from flood and riverbank erosion.DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14827 J. Environ. Sci. & Natural Resources, 5(2): 251-261 2012